1997
DOI: 10.1136/ip.3.2.89
|View full text |Cite
|
Sign up to set email alerts
|

An international study of the exposure of children to traffic.

Abstract: Objectives-To examine the extent of international differences in children's exposure to traffic as pedestrians or bicyclists. Design-Children's travel patterns were surveyed using a parent-child administered questionnaire. Children were sampled via primary schools, using a probability cluster sampling design.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 6 publications
1
29
0
2
Order By: Relevance
“…The majority of collision involving pedestrian age 17 and younger and 65 and older occurred near home. There is extensive pediatric literature addressing the proximity of child auto-pedestrian collisions to victims' homes or schools [Agran et al, 1994;Malek et al, 1990;Braddock et al, 1994;Roberts et al, 1997;Lightstone et al, 2001;La Scala et al, 2004].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of collision involving pedestrian age 17 and younger and 65 and older occurred near home. There is extensive pediatric literature addressing the proximity of child auto-pedestrian collisions to victims' homes or schools [Agran et al, 1994;Malek et al, 1990;Braddock et al, 1994;Roberts et al, 1997;Lightstone et al, 2001;La Scala et al, 2004].…”
Section: Discussionmentioning
confidence: 99%
“…Literature exploring child pedestrian injury suggests that collisions often occur close to children's homes or schools [Agran, Winn, Anderson, 1994;Malek, Guyer, Lescoheir, 1990;Braddock, Lapidus, Cromley, 1994;Roberts et al, 1997;Lightstone, Dhillon, Peek-Asa, 2001;La Scala, Guenewald, Johnson, 2004]. Additionally, past studies have identified factors associated with the risk of adult pedestrian collision and injury such as age and gender [La Scala, Gerber, Gruenewald, 2000;Graham, Glaister, Anderson, 2005;Hijar, Kraus, Tovar, 2001;Gorrie, Brown, Waite, 2008], alcohol involvement [La Scala et al, 2000;Shuurman, Cinnamon, Crooks, 2009;Paulozzi, 2006], and socio-economic status [Rivara and Barber, 1985;La Scala et al, 2000;Graham et al, 2005;Chakravarthy, Anderson, Ludlow, 2010] among others.…”
Section: Introductionmentioning
confidence: 99%
“…L'étalement urbain et la dépendance à l'automobile affectent de manière particulièrement sévère les enfants dans la mesure où l'utilisation des modes actifs de déplacement (aussi appelés « doux » en Europe) y est compromise (Hillman et Adams, 1992;Roberts et al, 1997). Ces modes sont en effet essentiels pour les enfants, car ils contribuent à leur prise d'autonomie et à leur développement (Fotel et Thomsen, 2003).…”
Section: Le Rapport Ville-campagneunclassified
“…Similarly, the likelihood that children engage in AST tends to decrease with increasing parental car ownership Roberts et al, 1997). Social norms (Lee et al, 2013;McMillan et al, 2007) and social support from friends have also been shown to be associated with AST (Hohepa et al, 2007;Hume et al, 2009;Panter et al, 2010a;.…”
Section: Social Environmentmentioning
confidence: 99%